2013
DOI: 10.1177/0960327113510536
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis induced by excessive coffee drinking

Abstract: Excessive ingestion of caffeine-containing beverages is a rare cause of rhabdomyolysis. Here, we describe the case of a 44-year-old woman presented with nausea, vomiting, palpitations, and tea-colored urine 6 h after drinking a liter of black coffee containing approximately 565 mg of caffeine for mental alertness. Laboratory studies were notable for myoglobinuria and markedly elevated plasma creatine kinase (CK) level of 7315 U/L. With volume expansion and alkalization, her plasma CK level returned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The clinical features of caffeine intoxication vary but have been reported to include cardiovascular symptoms (hypertension, hypotension, tachycardia, bradycardia, atrioventricular block, supraventricular tachycardia (SVT), ventricular tachycardia or ventricular fibrillation, myocardial ischemia, myocardial infarction, and cardiac arrest), gastrointestinal symptoms (nausea, vomiting, severe recurrent vomiting, abdominal pain, diarrhea), psychological/neurological symptoms (delusions, hallucinations anxiety, agitation, excitation, seizures, headache, cerebral edema, coma), metabolic symptoms (hypokalemia, hyponatremia, hypocalcemia, metabolic acidosis, respiratory alkalosis, hyperglycemia, fever), musculoskeletal symptoms (weakness, rigidity, tremor, rhabdomyolysis), pulmonary symptoms (hyperventilation, respiratory failure), tinnitus, dizziness, diuresis, and death [ 21 , [26] , [27] , [28] , [29] , [33] , [34] , [35] ]. Renal failure and questionable hepatic injury (i.e., based only upon modest transaminase elevation which is known to occur in cases of rhabdomyolysis) secondary to rhabdomyolysis have also been reported [ 36 , 37 ].…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical features of caffeine intoxication vary but have been reported to include cardiovascular symptoms (hypertension, hypotension, tachycardia, bradycardia, atrioventricular block, supraventricular tachycardia (SVT), ventricular tachycardia or ventricular fibrillation, myocardial ischemia, myocardial infarction, and cardiac arrest), gastrointestinal symptoms (nausea, vomiting, severe recurrent vomiting, abdominal pain, diarrhea), psychological/neurological symptoms (delusions, hallucinations anxiety, agitation, excitation, seizures, headache, cerebral edema, coma), metabolic symptoms (hypokalemia, hyponatremia, hypocalcemia, metabolic acidosis, respiratory alkalosis, hyperglycemia, fever), musculoskeletal symptoms (weakness, rigidity, tremor, rhabdomyolysis), pulmonary symptoms (hyperventilation, respiratory failure), tinnitus, dizziness, diuresis, and death [ 21 , [26] , [27] , [28] , [29] , [33] , [34] , [35] ]. Renal failure and questionable hepatic injury (i.e., based only upon modest transaminase elevation which is known to occur in cases of rhabdomyolysis) secondary to rhabdomyolysis have also been reported [ 36 , 37 ].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…In cases of metabolic acidosis and hypokalemia, sodium bicarbonate and potassium chloride have been used, respectively [ [36] , [37] , [38] ]. In the case of rhabdomyolysis, intravenous fluid resuscitation is most important but sodium bicarbonate might also be helpful [ 32 , [36] , [37] , [38] ].…”
Section: Management/treatment Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that excessive caffeine intake from energy drinks can cause arrhythmias, hypertension, dehydration, sleeplessness, nervousness, and in rare instances, rhabdomyolysis. In our literature search, only one case report of rhabdomyolysis caused by caffeinated beverages was found (3). Additional complications can arise depending on the individual's overall health status (e.g., cardiac conditions, diabetes and anxiety disorders) and other drugs or medications that patients may be taking (e.g., medications for attention deficit disorder).…”
Section: Discussionmentioning
confidence: 99%
“…Individual with preexisting anxiety disorders are more sensitive to the effect of Caffeine [43] . In rare cases, rhabdomyosis has been reported attributable to Caffeine [44,45] . It causes reduction in cerebral perfusion, that may sustain for 90 min of administration can thus reduce effectiveness of several drugs and can cause exacerbation in psychiatric illnesses in patient on maintenance therapy [46,47] .…”
Section: Effect Of Dte On Haloperidol-induced Catalepsymentioning
confidence: 99%